ANALISIS PEREKONOMIAN EMPAT SEKTOR : DAMPAK EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI - M. Irfan Rizqi; Cintia Febriliana Putri; Mala Millatina; M. Taufiq Abadi; Marfita Hikmatul Aini (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This journal analyzes the economic dynamics of 4 sectors with a focus on the influence of exports and imports. Through sectoral data analysis, this study identifies the role of each sector in driving export activity and its impact on the national economy. The findings highlight the complexity of the relationship between exports, imports, and economic growth, while exploring strategies to optimize the contribution of these sectors. The policy implications of the findings look towards sustainable economic development by taking into account the dynamic interaction between exports and imports in a 4-sector economy. The impact of exports and imports on economic growth in Indonesia is very large because exports are one of the sources of state income and from import activities the state can get goods that do not yet exist or are lacking in the country to meet the needs of the community. The analysis highlights the positive contribution of exports to economic growth, while the impact of imports is complex and requires careful handling. The policy implications of these findings are discussed in light of efforts to increase exports and manage imports to support sustainable economic growth in Indonesia.